Prevención y manejo clínico de pre eclampsia y eclampsia: Guía de práctica clínica basada en evidencias del instituto de referencia nacional en salud materna del Perú - Guevara Ríos, Enrique (2019)
Introduction. In Peru, hypertensive disorders of pregnancy are the second cause of maternal mortality. Objective. This evidence-based clinical practice guideline (EB-CPG) provides recommendations for the prevention and treatment of pre-eclampsia and eclampsia. Methods. An adapted EB-CPG was elaborated through a systematic, rigorous and transparent process with a group consisting of methodologists and health professionals who are experts in the management of the disease. The guide has sixteen clinical questions and sixteen recommendations. The search and pre-selection of EB-CPGs were performed, which were evaluated through the “Appraisal of Guidelines for Research and Evaluation II” tool (AGREE-II), for its adaptation. The systematic search for evidence to answer the 16 clinical questions were made in multiple databases: MEDLINE / PubMed, EMBASE / Ovid, Cochrane Library, LILACS and SciELO. Evidences were selected and analyzed critically by clinicians and methodologists in pairs, recommendations were elaborated through the Grading of Recommendations Assessment, Development, and Evaluation methodology (GRADE). Results. With the participation of a panel of clinical experts from the National Perinatal Maternal Institute, representatives from health care networks and other reference institutions, 16 recommendations were established for the prevention and treatment of pregnant women at risk of pre-eclampsia, for pregnant women with pre-eclampsia, eclampsia or hypertensive disease. Conclusions. This article summarizes the evidence-based clinical practice guidelines for the prevention and treatment of preeclampsia and eclampsia in peruvian pregnant women for the national reference institute for maternal and neonatal health of Peru.